Origin, distribution, and behaviour of rare earth elements in river bed sediments from a carbonate semi-arid basin (Tafna River, Algeria). (July 2019) - Benabdelkader, A.; Taleb, A.; Probst, J.L.; Belaidi, N.; Probst, A.
Abstract: The behaviour and sources of rare earth elements (REE) in river sediments were investigated at ten stations and two dams of the Tafna basin (Northern Algeria) during contrasting hydrological conditions and using a combination of normalisation procedures, REE anomalies, various REE ratios, and multivariate statistical analysis. The ranking and REE concentrations were in the range of other carbonated areas. The classical fractionation of the heavy REE(HREE) erosion pattern, evidenced from upstream to downstream by the La/Yb or Sm/Yb ratios, was disturbed by the presence of dams, which retained the light REE (LREE) in particular. The hydrological conditions, particle size, and geochemical characteristics controlled the REE patterns. The LREE were associated with clay minerals and HREE with coarse silts, whereas carbonate and particulate organic carbon (POC) did not influence the transport downstream. The total concentration of REE in sediments was not strongly affected by anthropogenic inputs from various sources (industrial activities, and domestic or medical wastes). Indeed, some LREE enrichment and anomalies were detected at a few stations and locally for Gd, Tb, and Yb. However, the anthropogenic contribution can partially be hidden by dilution due to particle erosion. High flow increased the LREE and MREE enrichment and LREE/HREE fractionation in some places due to erosion processes and anthropic influences (dam releases and local wastes inputs). Middle REE (MREE) and HREE were the most extractable elements unlike LREE (which are the most concentrated), particularly during high water conditions. Finally, the REE demonstrated the impact of natural processes (hydrological, geochemical, and physical) and some anthropogenic disturbances (waste inputs, fertilisers, and dams). This might inspire to develop such investigations in other similar semi-arid basins undergoing various pressures. The use of local bedrock as a reference and a set of geochemical and statistical tools, is recommended. Highlights: REE in river bed sediments were investigated from upstream to downstream. Hydrological conditions played a significant role on downstream REE transport. Erosion and particle size controlled REE, contrary to carbonates and COP. Dams stored LREE and disturb the LREE/HREE pattern downstream. Anthropogenic REE were not obviously detected in sediments, except Gd, Tb or Yb.